THE ROLE OF SCHOOLS IN PROMOTING ENVIRONMENTAL AWARENESS AND GREEN LIVING - Modjo, Ardiyanto Saleh (PT. Hafasy Dwi Nawasena, 2025)
Climate change and environmental degradation demand a strategic role for education in fostering environmentally conscious and sustainable behaviors among young generations. This study examines the role of schools in cultivating environmental awareness and green lifestyles through a Systematic Literature Review (SLR) approach. A total of 43 academic publications from 2019 to 2024 were analyzed through structured database searches and thematic analysis. The findings reveal that schools play a significant role in building ecological awareness through sustainability-integrated curricula, green school programs, project-based environmental learning, teacher modeling, environmentally oriented school culture, and community involvement. However, challenges remain, including limited school facilities, inconsistent implementation quality, and low digital green literacy. This research emphasizes that fostering sustainable behavior requires a systemic and collaborative approach to ensure the internalization of environmental values and habits among students.